The effectiveness of strategies for providing voter education in rural areas : a case study of Homu Village, Greater Giyani Municipality - Maswanganyi, Rirhandzu Bertha (My University, 2018)
Despite the adoption of democratic electoral procedures and the establishment of the Independent Electoral Commission (IEC) in post-apartheid South Africa, the strategies for providing voter education in rural areas of the country have not been adequate in terms of creating awareness about democracy and enabling rural citizens to mJlke rational choice during elections (Sadie, Patel, & Baldry 2016:6). It is for this reason that this study was conducted to evaluate the effectiveness of voter education strategies in one of the rural communities in Greater Giyani Municipality, in Limpopo province. This study adopted qualitative exploratory research design. The target groups were the local IEC voter educators and community members. Data was collected using one to one individual interviews, observation and literature review. The results of the study show that the IEC used various strategies to promote voter education. However, the dominant use of media was discredited by the community because of the language barrier, lack of ownership, one-way communication, unaffordability and low level of literacy. It was also found that voter education is not provided continuously as stated in IEC documents while shortage of IEC voter educators and limiting education periods pose other challenges. The study also revealed poor voter education coverage to special groups such as the disabled or the marginalised groups due to lack of capacity to teach them. These findings show that voter education is not as effective as it should be. The study therefore recommends that strategies for voter education be strengthened, especially in rural communities where people live in poverty and poor socio-economic conditions. It is further recommended that the IEC revises voter education strategies and uses those that will benefit more people, such as face to face and home visits, so that people feel free to ask questions. Furthermore, the community recommended that the IEC teaches community stakeholders, who will in turn cascade the information down to community members. The reason for this is that people are likely to feel free to communicate and to ask question because the educators will be known to them. The study further recommends that the IEC improves its staff complement to curb the existing shortage of human power. Further, research on evaluating the knowledge of voters on voting matters will be of outmost importance.
Thesis (MPA.) --University of Limpopo, 2018
Keywords: Voting; Voter education; Election; IEC; Rural areas; Education; Voting